Synthesis of Short, Self-Complementary DNA Oligomers and Solution Studies of their Duplex Structure and Formation - Visentin, Daniel (My University, 1984)
A phosphotriester synthesis for short deoxy oligomers was developed based on the RNA synthesis developed in Neilson's laboratory. This synthesis parallels that of Catlin and Cramer (1973) but differs significantly in a number of procedures and reagents used and represents an overall improvement in every aspect of the previous method. This synthetic procedure allows the synthesis of sufficient quantities of DNA for 1H-NMR analysis. The following sequences were successfully synthesized using this procedure: d(GCA) d(AGCT) d(ACGT) d(ACGTp) d (ACGTACGTp).
It was found by variable temperature 1H-NMR that the trimer and the tetramer duplexes had a very low Tm (0-10°C) as compared to their RNA counter-parts which had Tms between 29-34°C. This demonstrates quantitatively that the short DNA duplex is significantly less stable than the short RNA duplex. Consequently, sequences of at least five or six bases in length will be required for model studies of DNA duplex stabilities using variable temperature NMR methods.
A CD study of d(ACGTACGTp) in conditions of low salt (1M NaCl) and high salt (5M NaCl) demonstrated that a high salt B to Z-helix transition did not occur. Instead, the duplex remained in the right handed B form in both low and high salt.
Keywords: synthesis, DNA, oligomers, solution, duplex, structure, formation, phosphotriester, temperature